A Model for New Product Development in Business Companies Based on Grounded Theory Approach and Fuzzy Method - Nezhadkian, Mahyar; Azimi, Seyed Mohammadtaghi; Ferro, Andrea; Nafei, Amir Hossein (Journal of Computational and Cognitive Engineering, 2023)
This study aims to provide a model for new product development in business companies with a grounded theory approach and Fuzzy method. The present study was performed in the framework of a qualitative approach using the grounded theory method, and the required data were collected using in-depth interviews with experts. The study experts included university professors in marketing and senior executives in Beijing. The systematic method has three main stages such as open, axial, and selective coding. The obtained results demonstrate qualitative and technical improvement as the fundamental subject, brand and customer as the reason conditions, companies' marketing activities as the strategy, rules transparency and existing standards as the ruling context, managerial–promotional activities as the interfering factors, and new product and trust-building as the consequences in the paradigm model.